DETERMINATION OF THE EFFECT OF JOB SATISFACTION AND WORK MOTIVATION ON THE PERFORMANCE OF NURSES IN THE COVID-19 ENDEMIC - Prabowo, Wahyu Agung Setio; Herawati, Nuri (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
Nurses are the frontline against COVID-19, they take care of patients and are close to patients at all times. This research was conducted with the aim of knowing the direct impact of Job Satisfaction with Work Motivation, and Nurse Performance and its indirect effects in the post-pandemic period, namely the COVID-19 Endemic. The population used in this study were Nurses in one of the private hospitals in Sidoarjo, East Java, Indonesia, totaling 281 nurses. The sample in this study amounted to 109 respondents. The analysis technique used is using PLS SEM. From data processing, the results show that the Job Satisfaction variable has a significant role in fostering Work Motivation, and Nurse Performance in hospitals. Work Motivation is proven to affect performance. In addition, it turns out that Job Satisfaction indirectly affects Nurse Performance through Work Motivation of nurses. The results provide an understanding that the approach can be taken to maintain Nurse Performance, especially in difficult times such as endemic.